(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the expression of real life in the novel genre, one of the most important genres in Uzbek literature, based on the historical novel "Abu Rayhon Beruniy" by Isajon Sultan, one of the leading representatives of modern Uzbek literature. The work is notable not only for its artistic but also historical significance.